2016
DOI: 10.1177/0957926516676702
|View full text |Cite
|
Sign up to set email alerts
|

The representation of mental health sufferers in administrative and legal discourse

Abstract: This article examines the records of mental incompetence cases filed at a court of the first instance in Buenos Aires Province, Argentina. Using a Critical Discourse Analysis framework and qualitative methods, we explore the ways in which mental health sufferers are represented. Applying Tone Theory and Appraisal Theory (attitude/judgement subsystem) to our data, we distinguish two discursive zones. In one of them, subjects are constructed with linguistic resources that amount to inscribed expressions of negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Moreover, the construction of the biological incapability of those judged as "unaccountable mental patients" to possess a sociomoral value system positions them as biologically and morally inferior and distinguishes them from normal superior "others" (Olstead, 2002). Therefore, non-imputability is linked to their social ostracism, since they are judged as irresponsible and antisocial, because of their imputed inherent inability to distinguish between right and wrong (de Vel-Palumbo et al, 2021;Harding, 2012;Marchese & Celerier, 2017). Judicial discourse strips the person of their social traits, transforming them, as Margaritis (2015) argues, from a subject to an object of the law.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the construction of the biological incapability of those judged as "unaccountable mental patients" to possess a sociomoral value system positions them as biologically and morally inferior and distinguishes them from normal superior "others" (Olstead, 2002). Therefore, non-imputability is linked to their social ostracism, since they are judged as irresponsible and antisocial, because of their imputed inherent inability to distinguish between right and wrong (de Vel-Palumbo et al, 2021;Harding, 2012;Marchese & Celerier, 2017). Judicial discourse strips the person of their social traits, transforming them, as Margaritis (2015) argues, from a subject to an object of the law.…”
Section: Discussionmentioning
confidence: 99%
“…An individualistic depiction of "mental patients" is typical in criminal court trials, whereby the psychiatric risk-assessment of criminal recidivism lays the liability for committing the criminal act on them (Allely et al, 2019). Moreover, Marchese and Celerier (2017), when analyzing civil proceedings, found a polarized classification of people with psychiatric diagnoses as mentally competent or incompetent depending on their social adequacy, such as the ability to socialize and manage money. They also concluded that the marginalization of persons with psychiatric diagnoses in judicial discourse is maintained due to the prevalence of the medical model (Marchese & Celerier, 2017).…”
Section: Discourse Analysis Of Legal and Public Documentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such discriminatory practice resulted in poverty and dependency of disabled persons as they were excluded from the labor market. In the legal discourse, Marchese and Celerier (2017) examined the socio-discursive nature of records of mental incompetence cases filed at an Argentinian court. Persons with mental health issues were found inscribed with negative social judgments on their mental incapacity rather than mental capacity.…”
Section: Introductionmentioning
confidence: 99%